Three-component difluoroalkylation and trifluoromethylthiolation/trifluoromethylselenolation of π-bonds. Issue 10 (15th January 2018) - Zhang, Bo-Sheng; Gao, Lu-Yao; Zhang, Zhe; Wen, Yu-Hua; Liang, Yong-Min
Abstract : This report describes a new method for three-component difluoroalkylation and trifluoromethylthiolation/trifluoromethylselenolation of π-bonds via air-stable SCF3 and SeCF3 reagents as free-radical initiators of ethyl iododifluoroacetate. Abstract : This report describes a new method for three-component difluoroalkylation and trifluoromethylthiolation/trifluoromethylselenolation of π-bonds via air-stable SCF3 and SeCF3 reagents as free-radical initiators of ethyl iododifluoroacetate. β-Proton elimination can be overcome effectively in this reaction system, and a broad substrate scope, including alkenes and alkynes, makes this approach practical and attractive.